EFEKTIVITAS BANK WAKAF MIKRO DALAM MENGURANGI KEMISKINAN (Studi Kasus LKMS Denanyar Sumber Barokah) - Revita Adelia Safitri; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to investigate the effectiveness of Bank Wakaf Mikro (BWM) in reducing poverty. The case study approach on LKMS Denanyar Sumber Barokah. This study uses quantitative methods conducted by questionnaire tools to collect the data. The sampling method used was purposive sampling method and obtained 84 people. This study goes beyond data measurement using paired sample t-test. The findings of this study is BWM financing is effective in reducing poverty. Most of respondents can increase their income after receiving BWM financing. The results of this study indicate that products of BWM have helped the customers in reducing their poverty.Keywords: Sharia Microfinance, Micro Waqf Bank, Poverty